Prevalence And Determinants of Cognitive Impairment Among Rural Elderly Population of Aligarh - Mohd Maroof; Anees Ahmad; Najam Khalique; M Athar Ansari; M Salman Shah; Uzma Eram (Medsci Publications, 2016)
Introduction: Increase in life expectancy has resulted in increased proportion of elderly population. Elderly with Cognitive impairment have increased risk for progression to dementia and increased likelihood of contracting Alzheimer's disease than the general population. Objectives: To study the prevalence of cognitive impairment in elderly population & to determine the various socio- demographic factors associated with the cognitive impairment. Material & Methods: Community based cross- sectional study was done at field practice area of Rural Health Training Centre, JN Medical College, AMU, Aligarh by using systematic random sampling with PPS among 225 rural elderly individuals. Assessment of cognitive impairment was done using Mini Mental State Examination (Hindi version). Data was entered & analyzed using SPSS 20. Chi- Square test was used. P value <0.05 was considered significant. Results: The prevalence of cognitive impairment was found to be 16%. Significant relationship of the prevalence of cognitive impairment was observed with the age, gender, literacy status, & marital status. Conclusion: Approx. one- sixth of the elderly had cognitive impairment significantly related to various socio-demographic factors. Therefore, priority based care should be given to the vulnerable population by strengthening of the service available & creating awareness to utilize the services.